Determination Of The Malaysian Sharia Index In Health Aspects According To The Perspective Of Maqasid Sharia - Siti Khatijah Ismail; Lukman Abdul Mutalib (Human Resource Management Academic Research Societ, 2024)
Indexed by ERA